Post-translational regulation of FOXO - Xie, Qi; Chen, Jing; Yuan, Zengqiang (Acta biochimica et biophysica Sinica, 2012)
The Forkhead box O （FOXO） family transcription factors play critical roles in a series of cellular processes, including the cell cycle, cell death, metabolism, and oxidative stress resistance. FOXO proteins are subject to several post- translational modifications, which are closely related to their activity. In this paper, we review the post-translational modifications of FOXOs and their biological functions.